A Letter to Reconsider the Conditions for Testing Decontaminated N95 Respirators for Emergency Reuse to Address Shortage - Eric P. Vejerano; Jeonghyeon Ahn (Aerosol and Air Quality Research)
Abstract The battle with COVID-19 pandemic has resulted in the shortage of personal protective equipment, particularly, N95 respirators. Healthcare workers who reused N95 respirators may resort to unproven methods of cleaning/sterilization that can severely compromise the respirators’ filtration efficiency. A recently issued guideline will test decontaminated N95 respirators against particles with a median diameter of 0.075 ± 0.020 µm at a flow rate of 85 L min–1. For emergency reuse, these conditions may be too stringent. N95 respirators tested at this flow rate had predicted efficiencies of < 69%, assuming complete degradation of their electrostatic coating. Experimental efficiencies were ~15% lower. For emergency reuse, we recommend to either adjust the flow rate closer to normal breathing, or the size of the test particle should reflect that of virus-laden respiratory aerosols (~> 0.5 µm). By reconsidering the test conditions, a substantial fraction of used/decontaminated respirators can be reused.